HELPING PARENTS PARENTING CHILDREN WITH HEARING IMPAIRMENTS IN LEARNING - Surty Septriana (Jurnal Penelitian Pendidikan Khusus, 2015)
Abstrack: This research is motivated by problems that researchers have found in SLB Muhammadiyah Pauh IX Padang, the Deaf son F, X, Y and Z. In general, children disorders hearing will have lower achievement due to the difficulty to understand the language. However, deaf children of X, Y and Z are siblings who have talents in extracurricular areas. Therefore, research was conducted in order to determine parenting parents help children with hearing impairment in learning. This study used a qualitative descriptive approach, which focused on the implementation of the provision of livelihood, education and communication to parents of deaf children. The subjects were parents of X, Y and Z and SLB Muhammadiyah Pauh  IX school teacher in desert. The process of data collection in this study is done through observation and interviews. The results of this study are a parent trying to support every activity undertaken by children with hearing impairment. Activity communication parents with deaf children, although sometimes not relevant, but to each other try to make every communication that can be conveyed. They can develop talents for the assistance given by the school then motivation-motivation that is given by parents. Children experience in academic delay in the causes for the lack of repetition of existing school lessons at home. Therefore, parents are expected to provide guidance to their children, especially in the academic field. Kata kunci : Anak Tunarungu X, Y dan Z, Pola Asuh Orangtua, dan Bakat